Tata Kelola Kolaboratif Pengembangan Pariwisata Likupang, Kabupaten Minahasa Utara - Syahrifan Patadjenu; Mala Sondang Silitonga; Asropi (Ministry of Tourism and Creative Economy/Tourism and Creative Economy Agency Republic of Indonesia, 2023)
The development of tourism destinations is a series of multi-sectoral and multi-actor developments. Therefore cross-sectoral collaborative governance is needed to achieve common goals, as well as have an impact on the community's economy and regional development. This research focuses on answering questions (1) why is cross-sectoral cooperation between the government and non-government actors in the development of Likupang tourism not yet optimal? and (2) what is the collaborative governance model for Likupang tourism development? The research uses a qualitative approach with a case study method that took loci in Likupang, North Minahasa Regency. Collected primary data was through in-depth interviews with eight key informants. The development of Likupang tourism involves government and non-government actors. Likupang's collaborative governance model for tourism development focuses on the collaboration process as the partnership core. How the collaboration occurs, who the participants are, the division of duties and authorities, and the monitoring, evaluating, and reporting procedures must be clear and understandable to all parties. Institutional legality can clarify the task division so that each party will contribute to the partnership’s target achievement